Efektivitas Media Pembelajaran Interaktif Powerpoint terhadap Motivasi Belajar PJOK Siswa Kelas IV SDN Inpres O’o - Rafliansyah; Samsudin; Desy Ningsih Komalasari; Rabwan Satriawan; Mardian Andriani (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study was conducted based on the consideration that students' learning motivation in Physical Education, Sports, and Health (PJOK) still needs to be improved. In addition, the use of technology-based learning media in elementary schools has not yet been implemented optimally to support the teaching and learning process. One learning medium with the potential to enhance the quality of instruction is interactive PowerPoint-based learning media. By presenting learning materials in a more engaging and interactive manner, this medium is expected to encourage students to participate more actively during the learning process. Therefore, this study aimed to determine the effectiveness of interactive PowerPoint-based learning media in improving the learning motivation of fourth-grade students at SDN Inpres O'o.This study employed a pre-experimental research method using a one-group pretest-posttest design. The participants consisted of all 22 fourth-grade students, who were selected using the total sampling technique, meaning that the entire population was included as the research sample. Data on students' learning motivation were collected using a questionnaire administered before the treatment (pretest) and after the completion of the treatment (posttest). The collected data were analyzed using the Shapiro–Wilk normality test to examine the distribution of the data. The results of the analysis showed that the Asymp. Sig. (2-tailed) value was 0.000 (< 0.05). These findings indicate that the use of interactive PowerPoint-based learning media significantly improved the learning motivation of fourth-grade students in Physical Education, Sports, and Health (PJOK) at SDN Inpres O'o.